Population structure, growth, mortality and yield per recruit of segestid shrimp, Acetes japonicus (Decapoda: Sergestidae) from the coastal waters of Malacca, Peninsular Malaysia - Nurul Amin, Sanker Mohammad; Arshad, Aziz; Siraj, Siti Shapor; Bujang, Japar Sidik (2009)
Present study consists the population structure, growth, mortality and relative yield recruit of A. japonicus from the coastal waters of Malacca, Peninsular Malaysia. FISAT software has been used to examine the monthly data. The asymptotic length (La) and growth co-efficient (K) was estimated as 29.08 mm and 1.4 y-1. The growth performance index (φ) was calculated as 3.073. The exponent (b) of the length-weight relationship was found to be 3.063 (± 0.015). The asymptotic weight was calculated as 187.72 mg. Total mortality coefficient (Z) was estimated at 5.16 yr-1. The natural mortality (M) and fishing mortality (F) was calculated as 2.35 yr-1 and 2.81 yr-1, respectively. Exploitation rate (E) of A. japonicus was estimated as 0.54. The recruitment pattern was continuous throughout the year with one major peak. The relative yield per recruit analysis predicted the maximum exploitation rate (Emax) = 0.52. The current exploitation rate E is slightly higher than predicted Emax. The stock of A. japonicus was found to be over exploited in the investigated area.